(untitled) (Advancements in Homeopathic Research, 2024)
Background: Cervical spondylosis (CS) is a degenerative condition of the cervical spine found almost universally in persons over50 years of age. It has become one of the common problems globally.Methods: An experimental study was conducted on 60 patients diagnosed with cervical spondylosis as per the inclusion and exclusion criteria. All 60 cases of cervical spondylosis were randomized into 2 groups of 30 patients each. One group was prescribed with Individualized Homoeopathic medicine in decimal scale potency and the other group was prescribed with centesimal scale potencies of Individualized Homoeopathic medicine. The Remedy Response Evaluation Form was used to assess and interpret the follow up of the patients. The improvement of the patients was assessed by the Neck Disability Index (NDI). Result: Intra-group changes in NDI score were found statistically significant (P < 0.001, unpaired t test) group difference though favored centesimal against decimal. Conclusion: On statistical analysis, the p value was less than 0.001. Hence there is a significant difference between post treatment score of centesimal potency group as compared to decimal potency group.